1993
DOI: 10.1002/cm.970250407
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain dephosphorylation during cytokinesis in dividing sea urchin embryos

Abstract: Myosin heavy chain (MHC) phosphorylation was examined throughout the period of first cleavage in developing sea urchin embryos. MHC was found to be phosphorylated in these cells and, furthermore, the relative state of myosin phosphorylation was found to decrease as cells progressed through cytokinesis. Following the completion of cytokinesis, the relative state of MHC phosphorylation returned to levels observed in precytokinesis cells. The above results were obtained with myosin immunoprecipitated from whole c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that cells experience an increase in internal pressure as they enter cytokinesis (Burton and Taylor, 1997;Erickson and Trinkaus, 1976;Laster and Mackenzie, 1996). This is probably induced by the increased activity of myosin II during cytokinesis (Chen et al, 1994;Egelhoff et al, 1993;Larochelle and Epel, 1993;Pollenz et al, 1992;Satterwhite et al, 1992). Thus, cells must have enough tensile strength in their cortices to withstand the changes in internal pressure generated during cell division.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that cells experience an increase in internal pressure as they enter cytokinesis (Burton and Taylor, 1997;Erickson and Trinkaus, 1976;Laster and Mackenzie, 1996). This is probably induced by the increased activity of myosin II during cytokinesis (Chen et al, 1994;Egelhoff et al, 1993;Larochelle and Epel, 1993;Pollenz et al, 1992;Satterwhite et al, 1992). Thus, cells must have enough tensile strength in their cortices to withstand the changes in internal pressure generated during cell division.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that like in Dictyostelium [Egelhoff et al, 1993;Sabry et al, 1997], fission yeast [Motegi et al, 2004], and some mammalian cells [Rosenberg and Ravid, 2006], localization of myosin may be regulated through phosphorylation of myosin heavy chain on its tail in the sea urchin eggs. It has been reported that a phosphorylation level of myosin heavy chain is spatiotemporally regulated in the sea urchin eggs [Larochelle and Epel, 1993]. However, the relationship between the heavy chain phosphorylation and myosin localization remains to be investigated in the sea urchin egg.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clear throughout the animal kingdom and in protozoa that the mass of myosin II in the division furrow decreases steadily with furrow ingression, no mechanism has been identified in any other system that can explain this regulated disassembly. Dynamic changes in MHC phosphorylation levels within the contractile ring have been reported in dividing sea urchin embryos [35], suggesting that MHC phosphorylation as a mechanism regulating furrow myosin II disassembly may occur in other systems besides D. discoideum . We suggest that MHCK-C participates in this regulated myosin II filament disassembly in D. discoideum , and that this function may be regulated at both the cellular and biochemical level.…”
Section: Discussionmentioning
confidence: 99%